PENINGKATAN KETERAMPILAN BERBICARA BAHASA JAWA PADA SISWA KELAS 2A SDN PLEBENGAN DENGAN MENGGUNAKAN METODE MENDONGENG - Aswandari , Asih Aswandari; Agung Yuwono , Ahmad (Jurnal PGSD Indonesia, 2022)
This study aims to improve Javanese speaking skills through the storytelling method. This type of research is classroom action research. The research subjects were 23 class 2A students at SDN Plebengan. The object of research is the skill of speaking Javanese. The research design used was Kemmis and Mc. Taggart. The research was conducted in 2 cycles. Data collection techniques through the assessment of speaking skills. The data analysis technique used is descriptive quantitative. The results showed that the storytelling method could improve the Javanese language speaking skills of class 2A students at SDN Plebengan. This is evidenced by the increase in the results of the value of speaking skills cycle I and cycle II. The average value of Javanese speaking skills in cycle 1 meeting 1 was 76.09 cycle 1 meeting 2 was 80.44 so there was an increase in value of 4.35%. In cycle II meeting 1 the average value of speaking skills was 87.68, meeting 2 was 90.22 so there was an increase in value of 2.54%. From the results of the study it can be concluded that the storytelling method is effective in improving Javanese speaking skills in class 2A students at SDN Plebengan.